Relationships between group attachment and prosocial value with prosocial behavior tendencies among Orang Asli adolescents in Perak and Pahang, Malaysia - Ma'rof, Aini Azeqa (2013)
This study attempted to determine the relationships between group attachments (parental, peer, school and ethnic attachments), prosocial value (kindness) and prosocial behavior tendencies (altruistic and egoistic) amongst Orang Asli adolescents (secondary school students). The study involved a total number of 402 adolescents aged 14 years and 16 years from ten secondary schools in the states of Perak and Pahang. They were identified using Multi-Stage Cluster sampling technique. The study employed self-administrated questionnaire to collect data from the respondents by the guide of researcher. Findings showed that parental and ethnic group attachments were positively related to kindness and altruistic prosocial behavior but negatively associated with egoist ic prosocial behavior. Conversely, the findings indicated that peer attachment was negatively correlated with kindness and altruistic prosocial behaviors but positively associated with egoistic prosocial behavior. Prosocial value (kindness) on the other hand, showed significant relationships with both adolescents‟ altruistic and egoistic prosocial behavior tendencies. Meanwhile, prosocial value (kindness) had significant relationships with both adolescents‟ altruistic and egoistic prosocial behavior tendencies. In describing the relationship between variables, social exchange theory has been adopted. Moreover, a series of regression analyses indicated that kindness accounted for full mediation for the relationships between parental and peer attachments and altruistic prosocial behavior; but partially mediated the ethnic group attachment. Furthermore, the relationships between parental, peer and ethnic group attachments and egoistic prosocial behavior tendencies were fully mediated by kindness. Findings from this study also show that gender and ethnic group attachments were able to predict adolescents‟ altruistic prosocial behavior. Moreover, the study revealed that kindness was a unique predictor to both altruistic and egoistic prosocial behavior. However, school attachment did not give any significant value in this study. Findings from this study suggest that parental and ethnic group attachments play a significant role in affecting adolescents‟ altruistic prosocial behavior among Orang Asli adolescents. Their exposure to main-stream community influences their helping behavior, particularly their egoistic prosocial behavior. Moreover, kindness that act as mediating factor also play role on the relationships between group attachments and prosocial behavior tendencies. This study thus, provides valuable information on how society could enhance adolescent‟s prosocial behaviour and kindness through developing a secure attachment. In sum, the findings shed new light in the context of social psychology especially in prosocial behavior context among Orang Asli adolescents in acting egoistically or altruistically due to different types of social attachments and situations.